Peran Kontrol Tekanan Darah dalam Pencegahan Komplikasi Okular pada Pasien Hipertensi - Asmaul Husnah; Andi Kartini Eka Yanti; Azizah Anoez (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
Hypertension is one of the main risk factors that can cause damage to target organs, including the eyes. One of the complications that often occur in hypertensive patients is hypertensive retinopathy, which is damage to retinal blood vessels due to a persistent increase in blood pressure. This damage can be progressive and asymptomatic in the early stages, so it often goes undetected until severe visual disturbances appear. This study aims to identify and analyze the role of blood pressure control in the prevention of ocular complications in hypertensive patients through a literature review. The method used is literature review by selecting national and international research articles published in 2021–2025 from the PubMed, ScienceDirect, Google Scholar, and Cochrane Library databases. Inclusion criteria include full-text articles, relevant research designs, and discussing the relationship between blood pressure control and ocular complications. The results of the study showed that uncontrolled blood pressure increased the risk of retinal damage, decreased ocular perfusion, and microvascular changes detected through funduscopy and Optical Coherence Tomography Angiography (OCTA) examinations. Some studies have concluded that stable blood pressure control, not just the average value of blood pressure, has a significant effect in preventing the progression of hypertensive retinopathy. In addition, regular eye exams have been proven to be able to detect retinal changes early, so that preventive interventions can be carried out in a timely manner. Thus, optimal blood pressure control, therapy adherence, healthy lifestyle education, and regular retinal examinations are effective strategies in preventing ocular complications and maintaining vision quality in hypertensive patients.